Implementation of the Concept of Islamic Economic Equilibrium in Tagangser Laok Village: Between Spiritual Aspects and Community Welfare - Maisuri, Desi Endang; Jannah, Faridatul; Kamaroellah, R. Agoes (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This research examines the implementation of tawazun (equilibrium) principles in Islamic economics in Tagangser Laok Village, Waru District, Pamekasan Regency, Indonesia, to understand how rural communities balance material prosperity with spiritual values in their daily economic activities. Employing a descriptive qualitative approach, data were collected through in-depth interviews with traders, farmers, religious leaders, and small business owners, along with participant observation and document analysis. Findings reveal that the community has internalized tawazun values as foundational to economic behavior, understanding equilibrium as balancing income-earning with religious obligations. A religious leader articulated: